Areas of patent innovation regarding diabetic foot ulcers: technological prospecting. - Freitas, Vanessa Faria de; Mendes, Marcos Vinicius Silva; Neves, Sarah Ferreira; Colichi, Rosana Maria Barreto; Moraes, Juliano Teixeira; Ribeiro, Helen Cristiny Teodoro Couto (Investigación & Educación en Enfermería)
Objective. To identify areas of innovation in internationally registered patents focused on diabetic foot ulcers. Methods. This is a quantitative technological prospecting of international patents, from 2020 to 2024, in the World Intellectual Property Organization database, using the descriptor "diabetic foot". Results. 1372 patents were found, with the largest number of registrations originating from China (76.38%), the United States (4.74%), the Patent Cooperation Treaty (3.8%), and India (3.1%). The areas of innovation of the patents were classified into treatment (82.1%), prevention (12.2%), and evaluation (5.7%). Among the patents, 72.8% correspond to medical devices and 27.2% to pharmaceutical compounds. Conclusion. The global trend is towards patents for the treatment of diabetic foot complications.